PENGENDALIAN Aedes aegypti PADA DAERAH PERIMETER DAN BUFFER DI KANTOR KESEHATAN PELABUHAN SURABAYA - Shufo Shidiq Arinanto; Ngadino .; Hadi Suryono (GEMA LINGKUNGAN KESEHATAN, 2015)
Juanda Airport of Surabaya can be ragrded as a gathering point for travellers from various countries andtherefore contributes to the risk of global disease transmission. One of the transmissions may occur throughthe Aedes aegyptivector, a cause of Dengue Hemorrhagic Fever (DHF); as well as the yellow fever; both mayinduce death. The 2012 Annual Report of the Port Health Office of Surabaya showed that House Index,Container Index, and Bruteau Index in the buffer area remained over 1%, whereas the technical requirementsfor airports said that the perimeter area must be totally free of life vector and the buffer area indices must beless than 1%. The purpose of the present study was to indentify and assess the implementation of vectorcontrol programs in reducing the populations of Aedes aegypti at Juanda Airport of Surabaya. This study useddescriptive methods aimed at describing the implementation of Aedes aegypti control program at Juandaairport of Surabaya. The object of the study was the perimeter and buffer areas of Juanda Airport.Results showed that, of the six variables under study, 5 (five) variables of Aedes aegypti controlimplementation did satisfy the requirements. The variable on the mapping of Aedes aegypti breeding placesmet the requirements satisfactorily. The variables on larval surveys, adult mosquito surveys, counselingactivities, larvaciding and fogging did not satisfy the requirements. In conclusion, the implementation ofAedes aegypttontrol in Juanda Airport in 2014 did satisfy the designated requirements.It is recommended that Sedati Community Health Center and the Health Office of Juanda Airport of Surabayaimprove their existing cooperation so that the buffer area, which is under the responsibility of both entities,remains the target of surveillance in order for the area to be sterile of Aedes aegypti breeding, in accordancewith the standards and requirements as stated in the Decree of the Health Minister of Republic of IndonesiaNo. 431/Menkes/SK/IV/2007.